A Driftwood-Based Record of Arctic Sea Ice During the Last 500 Years From Northern Svalbard Reveals Sea Ice Dynamics in the Arctic Ocean and Arctic Peripheral Seas - Hole, Georgia M.; Rawson, Thomas; Farnsworth, Wesley Randall; Schomacker, Anders; Ingólfsson, Ólafur; Macias-Fauria, Marc (Journal of Geophysical Research: Oceans, 2021)
We present a 500-year history of naturally felled driftwood incursion to northern Svalbard, directly reflecting regional sea ice conditions and Arctic Ocean circulation. Provenance and age determinations by dendrochronology and wood anatomy provide insights into Arctic Ocean currents and climatic conditions at a fine spatial resolution, as crossdating with reference chronologies from the circum-Arctic boreal forests enables determination of the watershed the driftwood originated from. Sample crossdating may result in a wide range of matches across the pan-boreal region, which may be biased toward regions covered by the reference chronologies. Our study considers alternate approaches to selecting probable origin sites, by weighting scores via reference chronology span and visualizing results through spatiotemporal density plots, as opposed to more basic ranking systems. As our samples come from naturally felled trees (not logged or both), the relative proportions of different provenances are used to infer past ocean current dominance. Our record indicates centennial-to decadal-scale shifts in source regions for driftwood incursion to Svalbard, aligning with Late Holocene high variability and high frequency shifts in the Transpolar Drift and Beaufort Gyre strengths and associated fluctuating climate conditions. Driftwood occurrence and provenance also track the northward ice formation shift in peripheral Arctic seas in the past century. A distinct decrease in driftwood incursion during the last 30 years matches the observed decline in pan-Arctic sea ice extent in recent decades. Our new approach successfully employs driftwood as a proxy for Arctic Ocean surface circulation and sea ice dynamics.